Synthesis, structure and properties of N-R-amides and hydrazides of 2-[4-R-5-(3’-methylxanthine-7’-yl)-1,2,4-triazole-3-ylthio]acetic acid - Hotsulia, A. S.; Гоцуля, Андрій Сергійович; Гоцуля, А. С. (Запорізький державний медичний університет, 2018)
Introduction. Heterocyclic compounds are the foundation on which the creation of medicines is successfully carried out. One such system is 1,2,4-triazole and 3-methylxanthine. These heterocycles are characterized by wide range of biological properties, along with low toxicity. The purpose of this work was to synthesize and investigate the properties of N-R-amides and hydrazides 2-[4-R-5-(3’-methylxanthine- 7’-yl)-1,2,4-triazole-3-ylthio]acetic acid (R = CH3, C2H5, C6H5) when changing the conditions of the chemical process. Methods and results. As initial key reagents we used 7’-((3-thio-4-R-4H-1,2,4-triazole-5-yl)methyl)-3’-methylxanthine and ethers of 2-[4-R-5-((3’-methylxanthine-7’-yl)methyl)-1,2,4-triazole-3-ylthio]acetic acid, which were prepared according to known procedures from available raw materials. In the course of studies, it was found that when heated in ethanol the corresponding primary or secondary alkylamines (methylamine, ethylamine, monoethanolamine, diethylamine) or ammonia solution from prop-1-yl 2-[4-R-5-((3’-methylxanthine- 7’-yl)methyl)-1,2,4-triazole-3-ylthio]ethanoate, then the corresponding amidated derivatives of 2-[4-R-5-((3’-methylxanthine-7’-yl)methyl)- 1,2,4-triazole-3-ylthio]acetic acid are created. The corresponding amides were obtained by reacting 7’-((3-thio-4-R-4H-1,2,4-triazol-5-yl) methyl)-3’-methylxanthine with 2-chloroacetamide in a high yield sodium hydroxide medium. Hydrazides of 2-[4-R-5-((3’-methylxanthine-7’- yl)methyl)-1,2,4-triazole-3-ylthio]-ethane acid are synthesized by the interaction of the corresponding esters of 2-[4-R-5-((3’-methylxanthine- 7’-yl)methyl)-1,2,4-triazole-3-ylthio]acetic acid with an aqueous hydrazine hydrate solution in ethanol. The structure of the obtained compounds is confirmed by the data of elemental analysis, 1H NMR spectroscopy, IR-spectrophotometry. Individuality was established using thin-layer chromatography and chromatography-mass spectrometry. For synthesized compounds, preliminary screening was performed using the PASS On-line® software and molecular docking. The optimal methods for the preparation hydrazides and amides of 2-[4-R-5-((3’-methylxanthine-7’-yl)methyl)-1,2,4-triazole-3-ylthio]ethane acid were developed. The production of amides in two alternative pathways using the starting thiol and the ester, derived from it, was studied: it was established that the interaction of the starting thiol with 2-chloroacetamide runs with a larger yield of the reaction product in comparison with the reaction of the corresponding ester with ammonia. The results of physical-chemical analysis of synthesized compounds was interpreted. This preliminary assessment of the possible manifestation of anti-inflammatory activity was given. The probability of manifestation of this type of activity was not high. Conclusions. 19 amides and 3 hydrazide of 2-[4-R-5-((3’-methylxanthine-7’-yl)methyl)-1,2,4-triazole-3-ylthio]ethane acid were obtained with high yields and purity, their structure was proven and properties were investigated. Гетероциклічні сполуки – фундамент, на якому успішно відбувається створення лікарських засобів. Одними з таких систем є 1,2,4-тріазол і 3-метилксантин. Похідним цих гетероциклічних систем притаманний широкий спектр біологічних властивостей і невисока токсичність. Мета роботи – синтез і дослідження властивостей N-R-амідів і гідразидів 2-[4-R-5-(3’-метилксантин-7ʹ-іл)-1,2,4-тріазол-3-ілтіо]- ацетатної кислоти (R = CH3, C2H5, C6H5) при зміні умов перебігу хімічного процесу. Матеріали та методи. Як ключові вихідні реагенти використали 7’-((3-тіо-4-R-4Н-1,2,4-тріазол-5-іл)метил)-3’-метилксантин та ефіри 2-[4-R-5-((3’-метилксантин-7ʹ-іл)метил)-1,2,4-тріазол-3-ілтіо]етанової кислоти, які отримали за відомими методиками з доступної сировини. Результати. Встановили, що при нагріванні в етанолі відповідних первинних чи вторинних алкіламінів (метиламін, етиламін, моноетаноламін, діетиламін), розчину амоніаку з проп-1-іл-2-[4-R-5-((3’-метилксантин-7ʹ-іл)метил)-1,2,4-тріазол-3-ілтіо]етаноатом утворюються відповідні амідовані похідні 2-[4-R-5-((3’-метилксантин-7ʹ-іл)метил)-1,2,4-тріазол-3-ілтіо]етанової кислоти. Взаємодією 7’-((3-тіо-4-R-4Н-1,2,4-тріазол-5-іл)метил)-3’-метил-ксантину з 2-хлорацетамідом у середовищі розчину натрій гідроксиду з високи¬ми виходами одержали відповідні аміди. Гідразиди 2-[4-R-5-((3’-метилксантин-7ʹ-іл)метил)-1,2,4-тріазол-3-ілтіо]етанової кислоти синтезовані взаємодією відповідних естерів 2-[4-R-5-((3’-метилксантин-7ʹ-іл)метил)-1,2,4-тріазол-3-ілтіо]етанової кислоти з водним розчином гідразин гідрату в середовищі етанолу. Структура сполук підтверджена даними елементного аналізу, спектроскопії 1Н ЯМР, ІЧ-спектрофотометрії. Індивідуальність встановили за допомогою тонкошарової хроматографії та хромато-мас-спектрометрії. Для синтезованих сполук виконали попередній розрахунковий скринінг за допомогою програмного продукту PASS On-line® та молекулярного докінгу. Розробили оптимальні методи одержання гідразидів та амідів 2-[4-R-5-((3’-метилксантин-7ʹ-іл)метил)-1,2,4-тріазол-3-ілтіо] етанової кислоти. Дослідили одержання амідів за двома альтернативними шляхами з використанням вихідного тіолу та отриманого на його основі естеру: встановлено, що взаємодією вихідного тіолу з 2-хлорацетамідом перебігає з більшим виходом продукту реакції порівняно з реакцією взаємодії відповідного естеру з амоніаком. Інтерпретували результати фізико-хімічного аналізу синтезованих сполук. Здійснили попереднє оцінювання можливої появи протизапальної активності – імовірність не висока. Висновки. З високими виходами та чистотою одержали 19 амідів і 3 гідразиди 2-[4-R-5-((3’-метилксантин-7ʹ-іл)метил)-1,2,4-тріа¬зол-3-ілтіо]етанової кислоти, довели їх структуру та дослідили властивості. Гетероциклические соединения – фундамент, на котором успешно происходит создание лекарственных средств. Одними из таких систем являются 1,2,4-триазол и 3-метилксантин. Производным данных гетероциклов присущ широкий спектр биологических свойств наряду с невысокой токсичностью. Цель работы – синтез и исследование свойств N-R-амидов и гидразидов 2-[4-R-5-(3’-метилксантин-7’-ил)-1,2,4-триазол-3-илтио] ацетатной кислоты (R = CH3, C2H5, C6H5) при изменении условий протекания химического процесса. Материалы и методы. В качестве ключевых исходных реагентов использованы 7’-((3-тио-4-R-4Н-1,2,4-триазол-5-ил)метил)-3’-ме-тилксантин и эфиры 2-[4-R-5-((3’-метилксантин-7’-ил)метил)-1,2,4-триазол-3-илтио]-этановой кислоты, которые получены по известным методикам из доступного сырья. Результаты. В ходе исследований установлено, что при нагревании в этаноле соответствующих первичных или вторичных алкиламинов (метиламин, этиламин, моноэтаноламин, диэтиламин) или раствора аммиака с проп-1-ил-2-[4-R-5-((3’-метилксан¬тин-7’-ил)метил)-1,2,4-триазол-3-илтио]этаноатом образуются соответствующие амиды 2-[4-R-5-((3’-метилксантин-7’-ил)ме¬тил)-1,2,4-триазол-3-илтио]этановой кислоты. Взаимодействием 7’-((3-тио-4-R-4Н-1,2,4-триазол-5-ил)метил)-3’-метил-ксантина с 2-хлорацетамидом в среде раствора натрий гидроксида с высокими выходами получены соответствующие амиды. Гидразиды 2-[4-R-5-((3’-метилксантин-7’-ил)метил)-1,2,4-триазол-3-илтио]этановой кислоты синтезированы взаимодействием соответству¬ющих эфиров 2-[4-R-5-((3’-метилксантин-7’-ил)метил)-1,2,4-триазол-3-илтио]этановой кислоты с водным раствором гидразин гидрата в среде этанола. Структура полученных соединений подтверждена данными элементного анализа, спектроскопии 1Н ЯМР, ИК-спектрофотометрии. Индивидуальность установлена с помощью тонкослойной хроматографии и хромато-масс-спектро¬метрии. Для синтезированных соединений проведен предварительный расчетный скрининг с помощью программного продукта PASS On-line® и молекулярного докинга. Разработаны оптимальные методы получения гидразидов и амидов 2-[4-R-5-((3’-ме¬тилксантин-7’-ил)метил)-1,2,4-триазол-3-илтио]этановой кислоты. Исследовано получение амидов по двум альтернативными путям с использованием исходного тиола и полученного на его основе эфира: установлено, что взаимодействием исходного тиола с 2-хлорацетамидом протекает с большим выходом продукта реакции по сравнению с реакцией взаимодействия соответ¬ствующего эфира с аммиаком. Интерпретированы результаты физико-химического анализа синтезированных соединений. Дана предварительная оценка возможного проявления противовоспалительной активности – вероятность невысокая. Выводы. С высокими выходами и чистотой получены 19 амидов и 3 гидразида 2-[4-R-5-((3’-метилксантин-7’-ил)метил)-1,2,4-три¬азол-3-илтио]этановой кислоты, доказана их структура и исследованы свойства.
Синтез, будова та властивості N-R-амідів 2-[4-R-5-(3’-метилксантин-7ʹ-іл)-1,2,4-тріазол-3-ілтіо]ацетатної кислоти
Синтез, строение и свойства N-R-амидов 2-[4-R-5-(3’-метилксантин-7’-ил)-1,2,4-триазол-3-илтио]ацетатной кислоты
Keywords: 1,2,4-тріазол; 3-метилксантин; фізико-хімічні властивості; молекулярний докінг; 1,2,4-триазол; 3-метилксантин; физико-химические свойства; молекулярный докинг; 1,2,4-triazole; 3-methylxanthine; physical-chemical properties; molecular docking